2019
DOI: 10.1002/ejoc.201901408
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanoparticle‐Catalyzed Silaboration of Aryl‐Substituted Cyclopropyl Aldehydes Forming Rearranged β‐Boronate Silyl Enol Ethers

Abstract: 2-Aryl-substituted cyclopropyl aldehydes undergo an unprecedented Au nanoparticle-catalyzed silaboration leading to rearranged linear -boronate-bearing silyl enol ethers. For- [a] 7233 Scheme 6. Lack of reactivity in the attempted Au/TiO 2 -catalyzed silaboration of cyclopropanecarboxaldehyde (11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A year after that, this research group took advantage of this radical pathway in a gold-catalysed silaboration of arylsubstituted cyclopropyl aldehydes, which involves a radicalclock-type rearrangement (188a-f -189a-f, Scheme 59). 77 This gold-catalysed procedure proceeded smoothly in the presence of Au/Ti 2 O nanoparticles, providing a library of b-boronatetethered silyl enol ethers in synthetically useful yields. This silaboration products were found to be labile during the purification, delivering the corresponding aldehydes by hydrolytic deprotection.…”
Section: Scheme 59) B 2 Pin 2 Was Detected By Gc-ms Analysis As the mentioning
confidence: 99%
“…A year after that, this research group took advantage of this radical pathway in a gold-catalysed silaboration of arylsubstituted cyclopropyl aldehydes, which involves a radicalclock-type rearrangement (188a-f -189a-f, Scheme 59). 77 This gold-catalysed procedure proceeded smoothly in the presence of Au/Ti 2 O nanoparticles, providing a library of b-boronatetethered silyl enol ethers in synthetically useful yields. This silaboration products were found to be labile during the purification, delivering the corresponding aldehydes by hydrolytic deprotection.…”
Section: Scheme 59) B 2 Pin 2 Was Detected By Gc-ms Analysis As the mentioning
confidence: 99%
“…Our group has recently reported that the Au/TiO 2 -catalyzed silaboration of aryl-substituted cyclopropyl aldehydes gives acyclic β-boronate silyl enol ethers via ring-opening of the cyclopropane ring (Scheme ). A very similar ring-opening borylation concept with methoxypinacolborane has been reported more recently in the case of aryl cyclopropane carboxamides using Na metal as a one-electron donor . Given the facile activation of hydrosilanes on Au nanoparticles, which enables their addition on a variety of functional groups, in this manuscript, we report our studies regarding the reaction between cyclopropyl aldehydes or ketones with hydrosilanes using supported Au nanoparticles on titania (Au/TiO 2 ) as the catalyst.…”
Section: Introductionmentioning
confidence: 72%
“…The current example provides an additional paradigm of Au nanoparticle-catalyzed reactions in which ring-opening of the cyclopropane ring is observed. 14,21 Following the interesting hydrosilylation result of phenylsubstituted aldehyde 1a relative to parent 1b, we examined the reaction of PhMe 2 SiH with a series of aryl-substituted cyclopropyl carbonyl compounds (Table 1 connected to the aryl ring, even in the cases of substrates 1k and 1l, for which there is a methyl substituent on the adjacent cyclopropyl carbon. While an aryl substituent on parent cyclopropanecarbaldehyde (1b) appears necessary to obtain the ring-opening hydrosilylation pathway with selective cleavage of the cyclopropyl C(Ar)−C(carbonyl) bond, we also attempted to examine the influence of an alkyl group in the reaction outcome.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is a typical characteristic of Au/TiO 2 in a series of reactions involving silylboranes or bis( pinacolato) diboron. [3][4][5][6][7] The activation of the diboron reagent pinBBpin with nano Au(0) materials has been well established in its reaction with alkynes, 18 allenes 4 and methylene cyclopropanes. 19 The β-borylation of conjugated carbonyl compounds using pinBBpin as the boron source is also known in the literature applying several catalytic protocols.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we have additionally shown (Scheme 1) the regioselective silaboration of allenes, 4 the regioselective ring opening of epoxides and oxetanes yielding βor γ-silyloxy boronates respectively, 5 the pinacol-type reductive dimerization of aryl substituted carbonyl compounds promoted by the silylborane, 6 and more recently, the silaboration of 2-aryl-substituted cyclopropyl aldehydes, in which β-boronate silyl enol ethers are formed via ring-opening rearrangement of an intermediate α-silyloxy cyclopropyl radical. 7…”
Section: Introductionmentioning
confidence: 99%